Knockdown of LMTK3 in the Endometrioid Adenocarcinoma Cell Line Ishikawa: Inhibition of Growth and Estrogen Receptor α - Cai, Guiyang; Sun, Wei; Bi, Fangfang; Wang, Dandan; Yang, Qing (Frontiers in Oncology, 2021)
Abstract Objective The curative effect of high-efficiency progesterone and other therapeutic drugs for endometrioid adenocarcinoma patients with preservation of reproductive capacity has not been satisfactory so far. Novel therapeutic drugs need to be explored. Methods We investigated the cytoplastic and nuclear expression levels of LMTK3 between endometrioid adenocarcinoma tissues and normal endometrial tissues by immunohistochemistry. We detected the effects of LMTK3 on cell viability of Ishikawa cells by CCK-8. We detected the effects of LMTK3 on cell cycle and apoptosis of Ishikawa cells by flow cytometry. We also detected the effects of LMTK3 knockdown on mRNA and protein levels of ERα by qRT-PCR and western blotting, respectively. We also used cBioPortal online database to analyze the co-expression of LMTK3 and ESR1 in 1647 UCEC samples. Results We used TMAs to identify that the LMTK3 was mainly detected in cytoplasm of endometrioid tissues and cytoplasmic LMTK3 expression in endometrioid tissues was higher than that in normal endometrial tissues (P < 0.05). LMTK3 knockdown decreased the proliferation of Ishikawa cells through decreasing cell viability (P < 0.01), increasing G1 (P < 0.001) arrest and promoting apoptosis (P < 0.01). There was a positive correlation between the mRNA expression levels of LMTK3 and ESR1 (Spearman: P=2.011e-5, R=0.13; Pearson: P=7.18e-8, R=0.17). Knockdown of LMTK3 also reduced the mRNA (P < 0.001) and protein (P < 0.001) levels of ERα. Conclusions Inhibitors of LMTK3 may be as a possible future treatment for ERα and LMTK3 high expressed endometrioid adenocarcinoma followed appropriate studies.